Diabetes Disease in Geoff Marsh Film Documentary, Implication for Sub-Sahara Africa and the International Community - Adjeketa, Blessing; Adjeketa , Theophilus; Enita, Godfrey; Shireku , Alphonsus (The Journal of Society and Media, 2025)
The global burden of non-communicable diseases is increasing daily. Non-communicable diseases like hypertension, cancer, and diabetes have caused the death of more people in 21st-century sub-Saharan Africa than it has ever done. Also, the world celebrates 100 years of insulin, however, many, children and people in the Sub-Sahara with type 1 and type 2 diabetes die for lack of access to insulin or diabetes medications. Worse yet, the present status of diabetes in Sub-Saharan Africa is not well-known. The article uses content analysis and agenda-setting theory to examine Geoff Marsh's documentary on diabetes in Sub-Saharan Africa.. The documentary was produced with the support of AstraZeneca, Medtronic, and copyrighted by Springer Nature LTD 2021 (the video was downloaded from YouTube). The analysis of the documentary linked the death toll resulting from diabetes to a change in lifestyle and the government's meagre budget for the health sector in Sub- Saharan Africa. Filmmakers in the Sub-Saharan region should advocate and prioritize the maintenance of a healthy personal diet, engage in regular physical exercise, and maintain a normal body weight in their films. Sponsored radio and television programs focusing on managing and preventing the disease are needed across countries in the sub-Sahara